Chemically activated carbons derived from cashew nut shells as potential electrode materials for electrochemical supercapacitors - Chaiammart, Nattapat; Vignesh, Veeramuthu; Thu, Myo Myo; Eiad-ua, Apiluck; Maiyalagan, Thandavarayan; Panomsuwan, Gasidit (My University, 2025)
Supercapacitors are widely recognized as energy storage solutions due to their high power densities and long cycle lives. Furthermore, there is growing scientific and technological interest in converting biomass waste into carbon materials for manufacturing supercapacitor electrodes. In addition to their abundance and cost-effectiveness, the appeal of carbons derived from biomass lies in their tunable porosity, which enables the rational design of carbon materials to achieve the desired performance of supercapacitors. Here, we present the synthesis of activated carbons from cashew nut shells via potassium hydroxide (KOH) activation at different temperatures (650, 750, and 850 °C). The resulting materials exhibited amorphous and predominant microporous structures. Increasing the activation temperature led to a rise in specific surface area from 1534 to 2034 m2 g−1 and an increased proportion of mesopores. The electrochemical properties of these activated carbons for supercapacitor applications were investigated by cyclic voltammetry, galvanostatic charge–discharge, and impedance spectroscopic techniques in a 1 M sodium sulfate (Na2SO4) electrolyte. Using a three-electrode system, the activated carbons treated at 750 °C exhibited a maximum specific capacitance of 106 F g−1 at a current density of 0.5 A g−1 with a good rate capability; they retained 75 % at 10 A g−1 over a 1.0 V voltage window. Furthermore, a symmetric supercapacitor coin-cell, fabricated with activated carbons treated at 750 °C as the positive and negative electrodes, demonstrated an energy density of 2.43 Wh kg−1 at a power density of 1002 W kg−1. The cell exhibited 87 % capacitance retention at 1.0 A g−1 after 10,000 cycles. This work showcases the efficient and sustainable utilization of cashew nut shells as a carbon source for supercapacitor applications and highlights their value in a circular economy.
Keywords: Activated carbons; Cashew nut shells; Chemical activation; Supercapacitors